Expression of foot and mouth disease virus nonstructural polyprotein 3ABC with inactive 3C pro in Escherichia coli - Ladawan Sariya (2018)
Nonstructural 3ABC protein of foot and mouth disease virus (FMDV) was widely used to differentiate vaccinated from natural FMDV-infected animals. 3ABC is a polyprotein which is auto-processed to 3A, three copies of 3B and 3C pro by 3C pro protease. The 3ABC gene was cloned and expressed in Escherichia coli as native or mutated 3ABC (mu3ABC) forms. Cysteine residues 142 and 163 of the catalytic triad within the 3C pro of mu3ABC were changed to serine and glycine, respectively, to inhibit its protease activity. Both native and mutated 3ABC ORFs were cloned into BamHI and HindIII restriction sites of an expression vector, pQE 80L. The expression of the recombinant native 3ABC and mu3ABC genes in E. coli BL21 was induced with 0.2 mM isopropyl-beta-d-thiogalactopyranoside at 37 °C for 5 h. SDS-PAGE and Western blot analysis revealed that the full length 3ABC was present in the lysate from mu3ABC but not native 3ABC transformed cells. The recombinant mu3ABC was expressed mainly in the inclusion body and presented as monomer and dimer. In addition, the mu3ABC reacted strongly with a convalescent serum from a natural FMDV-infected cattle but very weakly with a serum from vaccinated cattle. This study clearly demonstrates that successful expression of the full length 3ABC occurs only when the protease active sites within the 3C pro were completely abolished. This information would accelerate in house development of the 3ABC-based diagnostic test that can distinguish between vaccinated and FMDV-infected animals. © 2011 Elsevier Inc. All rights reserved.